A defective one-dimensional superconducting photonic crystal design for the generation of the Fano resonance feature. (12th October 2020) - Mohamed, Asmaa M; Sabra, Walied; Aly, Arafa H; Mobarak, M; Shalaby, A S
Abstract: In the present work, we demonstrate the generation of Fano resonance (F) feature based on a defected one dimensional superconducting photonic crystal design. Our proposed design consists of alternated layers of high-temperature superconductor material with conventional ones. By using the transfer matrix method, we investigate the optical properties for the proposed designs. The obtained optical properties show two sharp peaks with zero side band of reflectivity are resulted NIR region. Then, by adding a defect layer to the periodic structure, we find that two peaks are appeared in the obtained spectrum which they are indicated for electromagnetic induced reflection (EIR) and Fano resonance concept. Finally, by adjusting the design parameters of our proposed structure such as the number of periods, the thickness of the constituent layers, and the refractive index of defect layer, we investigated the corresponding optical properties response. Our proposed designs can be used in some potential applications such as in the optical devices as switching, slow-light and sensor.